Development of Competency-Based Instruction in the Challenging Era: A Case Study of French for Airline Ground Services - CHITKLA, Kantaphong (Pattimura University, 2022)
In this decade, the world faces to several challenges such as economic volatility and transformation of work styles and lifestyle changed at the moment. It is undeniable that the travel by plane is in high demand before and after Covid-19. The airport ground services need competent personnel. The teaching of French at the university does not neglect these situations. French Program of Khon Kaen University created the French for Airline Ground Service course in 2011. Nowadays, this course opens its doors to accommodate 80 percent of the 3rd year of French major. It is interesting to study the development of the course and analyze the teaching and learning methods. This research was based on the action-oriented approach to pedagogy and teaching on the basis of competence. The results show that this course offers learners French at the B1+ level of CEFR and the basic skills for the airport ground staff in relation to the Rome N2201 of the Pôle Emploi of French Republic. In terms of learning activities, learners follow the Interaction Mode of Instruction to acquire life and career skills. Moreover, the software applications on flight preparation: Flightradar24 and Windy are used in the learning activities. This brings the learners to practice digital language and technology. Nevertheless, this research lacks the satisfaction of the airline entrepreneurs